Anak dan Kekerasan Seksual: Peran Konselor dalam Penyembuhan Traumatik Pada Anak Korban Kekerasan Seksual - Anis Fa’iqoh; Nina Fitriyani; Pahlevi Reza (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2023)
Judging from the data for the last two years, namely in 2021 and 2022 from the Banten Provincial Child Protection Agency (LPA) regarding sexual violence, it shows that hundreds or even thousands of cases of sexual violence against children have been found. This is what drives the writer to provide new knowledge and understanding to readers to recognize the trauma experienced by victims of sexual harassment. In this case the role of a counselor with the right assistance will be a form of psychological treatment that can reduce the suffering of victims. In this study the authors used qualitative research methods with a type of literature study. Qualitative research is research that is used to examine a natural object. Literature study is research that is carried out only on the basis of written works, including the results of both past and unfinished research